'Debordering' and 'rebordering': discriminatory and racial discourses of borders under globalisation. (2016) - Melin, Raedene
Recent academic research suggests that our world has transformed from one structured around the borders of nation-states to one that has become 'borderless' under globalisation. Neoliberalism has significantly reduced the power of nation-states as international institutions and agreements have established themselves as the leaders of global policy and the promoters of free trade and economic liberalisation. Governments, corporations and institutions in the global north experience a process of 'debordering' through international agreements that tear down barriers to trade and allow the further exploitation of populations and economies of the global south. In contrast, the global south endures a process of 'rebordering' through the barriers, physical and otherwise, constructed to keep racialised and poor bodies out of the global north and in their position as the disposable 'other', proving that the distribution of the benefits of neoliberalism are racialised and unequal.